Legal History and Legal Scholarship - Stuart Banner (Washington University Law Quarterly, 1998)
I wish to suggest that the legal history written today is similar in one important respect to today's most highly esteemed forms of conventional legal scholarship, and that this similarity is paradoxically the reason for the familiar gulf between the two. By conventional legal scholarship, I mean work appearing in law reviews that falls comfortably within the disciplinary conventions of academic law, work that does not purport to straddle the boundary between law and some other academic discipline. As I will make clear below, much of this work is not conventional in any other sense. My comparison of this sort of legal scholarship with legal history is not intended to disparage either mode of writing, or to imply that the gulf between them ought to be bridged. I aim only to describe a seldom-noticed by-product of the disciplinary self-conceptions of academic law and history, and to provide an explanation for it.
Keywords: Law -- History; Law -- Study & teaching; Legal history